2000
DOI: 10.1007/s004670050028
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic collapsing glomerulopathy in children

Abstract: Idiopathic collapsing glomerulopathy (ICG) is a clinically and pathologically distinct variant of focal segmental glomerulosclerosis, characterized clinically by rapid progression of renal insufficiency, a male and African-American racial predominance, and pathologically by segmental glomerular collapse, visceral epithelial cell hypertrophy and hyperplasia, and the absence of endothelial tubuloreticular inclusions. Pathologically similar lesions have been reported in adult and pediatric patients with human imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
25
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 15 publications
(64 reference statements)
6
25
1
Order By: Relevance
“…Compared with other variants of FSGS, collapsing FSGS is less responsive to steroids and other immunosuppressive drugs. According to most previous reports, the prognosis is usually poor, and patients are more likely to be in end-stage renal disease within a few years in spite of therapy (13,14). Kaito et al reported a case with steroid-and cyclosporin-resistant collapsing FSGS who went into complete remission with a combination rituximab and steroid pulse-therapy while receiving CyA (15).…”
Section: Discussionmentioning
confidence: 99%
“…Compared with other variants of FSGS, collapsing FSGS is less responsive to steroids and other immunosuppressive drugs. According to most previous reports, the prognosis is usually poor, and patients are more likely to be in end-stage renal disease within a few years in spite of therapy (13,14). Kaito et al reported a case with steroid-and cyclosporin-resistant collapsing FSGS who went into complete remission with a combination rituximab and steroid pulse-therapy while receiving CyA (15).…”
Section: Discussionmentioning
confidence: 99%
“…However, today we know that under certain circumstances both adults and children not infected with HIV-1 can develop similar lesions [144,145]. Thus, it is tempting to speculate that other infectious agents may be involved in the pathogenesis of collapsing FSGS.…”
Section: Opportunistic Infections As Co-factors Of Hivanmentioning
confidence: 93%
“…In general, there is a poor response to steroids [12,13,14]. However, remission is achievable in some patients with other immunosuppressive therapy [14,15,16]. While there have been reports of efficacy for rituximab in FSGS (for example, Kaito et al [17] reported a case of a 2-year-old boy with steroid- and CsA-resistant collapsing FSGS who went into complete remission with a combination of intravenous rituximab and MP pulse therapy while receiving oral CsA), we were unable to offer rituximab in this case.…”
Section: Discussionmentioning
confidence: 99%
“…Our patient progressed very quickly to ESRF. It was reported previously that the prognosis is usually poor and that patients are likely to be in ESRF within a few years despite receiving treatment [15]. …”
Section: Discussionmentioning
confidence: 99%